THE RESPONSIVE LEGISLATION: THE ROLE OF PARLIAMENTS IN THE ESTABLISHMENT OF LOCAL REGULATIONS ON TAXES AND FEES THAT ARE RESPONSIVE IN CENTRAL MALUKU DISTRICT - Dayanto, Dayanto; Ruslan, Achmad; Hasrul, Muh.; Hakim, Asma (Tadulako University, 2016)
The existence of Local Regulation of taxes and levies is often a problem, especially the cause of the economic climate, hight cost economy in the era of regional autonomy widespread today. Therefore, the Regional Representatives Council as one of the primary organs of the establishment of legislation demanded its role in presenting the Regulation on Taxes and Levies responsive. With the normative-legal research methods-empirical located in Central Maluku district, the study found that the normative role of Parliament as provided for in the provisions of legislation that allows for the formation of local legislation on taxes and levies which have not been effectively implemented responsive. Therefore, to ensure the establishment of local legislation on Taxes and Levies character responsive required their obedience to the law of Parliament to implement the role of normative in the formation of legislation, empowering the institutional capacity of Parliament as well as personal legislators in the formation of legislation, as well as the necessary revision of DPRDÂ Regulation Central Maluku District Number 01 of 2014 on the Standing Orders of parliament so as to ensure the accessibility of public participation in the formation of legislation.